Biophysical and structural characterisation of protein-peptide interactions - Brown, Peter N. (The University of Edinburgh, 2010)
Proliferating cell nuclear antigen (PCNA) is an essential protein in the cell. It is involved in transcription and many types of DNA repair and replication. Homologues of this protein are found in all orders of life. The high level of conservation and essential nature of PCNA infers that it may be a potential drug target for anti-caner drugs in humans and also a potential anti-parasitic target. X-ray structures of PCNA from Homo sapiens (Hs), Schizosaccharomyces pombe (Sp) and Leishmania major (Lm) are now available and can be used as a template for structure based drug design. In this work PCNA from these three species have been prepared in milligram quantities for biochemical and biophysical studies. The previously unknown structure of LmPCNA has been solved in an uncomplexed form and also complexed with a dodecapeptide to a resolution of 3.0Å. A comparison of PCNA structures and their peptide complexes for the three species identifies structural differences which may be relevant in analysing thermodynamic contributions of binding. All eukaryotic PCNA molecules exist as ring shaped trimers which form around DNA. In this work the oligomeric state of LmPCNA has been determined to be hexameric both in solution and in the crystal. It has also been hypothesised that HsPCNA is hexameric however these would seem to form hexamers in which the trimeric rings associate “back-to-back” while LmPCNA trimers would seem to associate “face-to-face”. The binding affinities for these three PCNAs have been determined with a selection of peptides derived from the Hs p21 protein. This work has shown, using a selection of different techniques including Surface Plasmon Resonance (SPR), Isothermal Titration Calorimetry (ITC) and Dynamic Scanning Fluorimetry (DSF); that HsPCNA and SpPCNA have similar affinities for a 12mer peptide (Kd of ~1μM) however LmPCNA shows significantly weaker interactions (Kd of ~10μM). This is most likely due to divergence in the sequence and structure of LmPCNA. A systematic investigation by SPR on the effect of peptide linker length on binding has been carried out using a series of synthesised peptides with different lengths of chemical spacer. The series of streptavidin immobilised peptides show that longer spacers are required for the recovery of the PCNA peptide binding affinity. The results presented in this work indicate that a linker length of at least 20Å is required for measurable protein binding activity. This interaction is improved with longer peptide spacers.
Keywords: peptides; affinity; Surface Plasmon Resonance; Dynamic Scanning Fluorimetry; thermodynamics; SPR